Measurement of the thermal conductivity of flexible biosourced polymers using the 3-omega method. (September 2018) - Boussatour, G.; Cresson, P.Y.; Genestie, B.; Joly, N.; Brun, J.F.; Lasri, T.
Abstract: The thermal conductivity of flexible biosourced polymers was measured by the 3-omega method. Two biopolymers were investigated: the polylactic acid (PLA), a widely used commercial biodegradable one, and the cellulose palmitate (CP), a hydrophobic biosourced material developed in the laboratory, that could be used in electronic or microfluidic applications. The 3-omega method is based-on the use of a metal element as both heating device to thermally disturb the system and temperature sensor. A stencil lithography technique was applied to obtain metallic lines, since biopolymers are not compatible with classical photolithography method. Thermal conductivities of 0.19 and 0.30 W/m.K are obtained respectively for PLA and CP thick films, and 0.12 and 0.22 W/m.K for respectively PLA and CP thin films. These values are close to those measured for petro-sourced substrates or films and so give the possibility to address the applications mentioned. Highlights: 2 biosourced polymers are studied: PLA and the cellulose palmitate (hydrophobic). Thermal conductivity measurement of thin (thickness < 1μm) and thick (<1 mm) biopolymers films by using 3-omega method. A stencil lithography technique has been applied to obtain metallic lines. Realization of flexible substrates to replace petro-sourced polymers (Polyimide, PEN…) for electronic devices.